The use of a private company to promote and develop the property interests of rural communities - Schoeman, W (University of Limpopo, 2018)
The aim of this study is to posit the theory that it will be more beneficial to, rather use a private company instead of a Communal Property Association (CPA) to promote and develop the property interests of previous disadvantaged rural communities. Maladministration, poor governance, misappropriation of funds and property together with diverging interests give rise to disputes and internal conflict. The research will include a literature study of relevant textbooks, case law, law journals, legislation and discussion documents. Constitutional development in property law opened the door for a different approach in the application of property rights and rights relating to property, which in return precedes to a better understanding of communal rights and the enforcement of traditional values in a democratic society. Despite these constitutional developments, the maladministration, poor governance and misappropriation of funds and property by Communal Property Association executive committees caused discontent amongst community members, necessitating the examining of the use of a private company to promote and develop the property interests of rural communities, as an alternative institution to enhance democracy and the protection of human rights in communal context. The development of, either proper legislation to ensure compliance with the principles of good governance, accountability and transparency or the use of an alternative institution, which is already required by law to comply with the said principles, to manage the affairs of a Communal Property Association, should resolve these problems. The study is primarily a critical analysis and comparative study on the relevant provisions of the Companies Act 71 of 2008 in relation to the provisions of the Communal Property Associations Act 28 of 1996 to establish whether the use of a private company can resolve the problems currently experienced by Communal Property Associations.
Thesis (LLM.) -- University of Limpopo, 2018
Keywords: Private company; Rural communities; Private company; Rights of property